ANALISIS PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI PROVINSI JAWA TENGAH - Rochmani, Tanti Siti; Purwaningsih, Yunastiti; Suryantoro, Agustinus (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
The purpose of this study was to analyze the factors affecting employment in the industrial sector of Central Java province. Research backdrop that aspects of employment is a fundamental aspect in the economy. The economy is growing through the process of industrialization, should be able to absorb a lot of labor. With more and more workers absorbed there will be an increase in welfare of the population. This study is an analysis of secondary data such as time series data for 2010-2014. The analysis technique used is the panel data regression. The results showed the rate of economic growth and the minimum wage Regency / City positive effect on employment, while the number of industrial business unit does not affect the employment of industrial sector in the province of Central Java. Keywords: employment, economic growth, minimum wage, industry, Central Java